Comparison of Objective Intermediate-Term Outcomes Between per-Oral Endoscopic Myotomy and Laparoscopic Heller Myotomy Show Equivalence. (June 2021) - Ward, Marc A.; Clothier, Jessica S.; Ebrahim, Ahmed; Ogola, Gerald O.; Leeds, Steven G.
Introduction. The surgical gold standard for esophageal motility disorders is laparoscopic Heller myotomy (LHM). Per-oral endoscopic myotomy (POEM) is a less invasive flexible endoscopic alternative. We compare their intermediate-term outcomes. Methods. Data were collected on consecutive LHM and POEM patients treated for esophageal motility disorders from January 2015 to December 2019. All patients were invited for a comprehensive workup between 6 and 12 months post-myotomy including symptom evaluation, pH testing off medications, manometry, and esophagogastroduodenoscopy (EGD). Primary outcomes include swallowing function and development of postoperative gastroesophageal reflux disease (GERD). Results. There were 100 patients (46 LHM and 54 POEM). Patient demographics and presenting symptoms were comparable. Follow-up data were obtained from 49% of patients. Average length of follow-up for all patients was 10 months. Mean Eckardt scores for LHM decreased from 6.6 to 2.4 ( P < .05) and from 7.06 to 2.2 for POEM ( P < .05). Mean integrated relaxation pressure decreased from 22.8 preoperatively to 11 postoperatively in LHM patients and from 24.6 to 11.5 in POEM patients. POEM patients had a lower incidence of objective postoperative GERD with lower average DeMeester scores (20 vs 29.4) and a higher percentage of patients with a normal DeMeester score (47% vs 31%) compared to LHM patients. However, postoperative GERD health related quality of life scores (11.7 vs 14.1), the percent of patients on proton pump inhibitors (PPIs) (40% vs 53%), and frequency of grade C/D esophagitis (4.3% vs 5.6%) were lower in LHM patients. Conclusions. Intermediate-term symptom resolution and esophageal physiology are improved equally with both procedures. The development of postoperative GERD is equivalent.